Systematical analysis of (n,2n) reaction cross sections for 14-15 MeV neutrons - Ch, Saikhanbayar; M, Odsuren; G, Khuukhenkhuu (Scientific transaction of the National University of Mongolia. Physics, 2022)
Fast neutron induced nuclear reaction cross section data are necessary for both nuclear energy technology and the understanding of fundamental nuclear physics problems. The information of (n,2n) cross sections is quite essential in nuclear technology as a significant portion of the fission neutron spectrum lies above the threshold of (n,2n) reaction for most of the reactor materials. These cross section data are required in shielding and breeding calculations. Radioactive nuclides produced in the reactor usually have short half-life. So, direct measurement of their neutron cross sections is difficult. Therefore, model formulae are important to predict these cross sections theoretically. In this work, in the framework of the statistical model we deduced some theoretical formulae for the (n,2n) cross section using the evaporation model, constant nuclear temperature approximation and Weizsäker’s formula for binding energy. The model formulae were utilized for systematical analysis of known experimental data of the (n,2n) cross sections at 14 - 15 MeV energy.